KEMAMPUAN REPRESENTASI MATEMATIS MAHASISWA DALAM MENYELESAIKAN MASALAH STATISTIKA BERDASARKAN LANGKAH KRULIK DAN RUDNICK - An nur Ami Widodo; Dedi Nur Aristiyo (Jurnal Edukasi dan Sains Matematika (JES-MAT), 2019)
This research intended to describe the mathematical representation of students in solving statistical problems based on the Krulik anf Rdunick steps. This research is a qualitative descriptive study. The subjects of this study were students of the second semester mathematic education study program. The procedure of subjects using purposive sampling techniques. Data collection techniques in this study were observation, interviews and documentation. Data validity used triangulation. Data analysis techniques using the Mile and Huberman step, namely data reduction, data presentations, drawing conclusions and verifyingconclusions. The results The results of this study are as follows: (1) subjects with high ability in the read and think and exploration and plan stages, using verbal and symbolic representations. The stage of select a strategy, using symbolic representation. The find and answer stage, uses symbolic and visual representations. In the reflect and extend step, the subject uses verbal representations. For students with moderate ability in the stage of read and think and explore and plan using verbal representation. The stage of finding an answer and select a strategy using verbal and symbolic representation. The reflect and extend stage of the subject uses symbolic representations. In students with low ability to read and think and explore and plan using verbal representation. Stage select a strategy subject using symbolic representation.